Second World, Second Sex Socialist Women's Activism and Global Solidarity During the Cold War - Ghodsee, Kristen Rogheh 1970- (Duke University Press, 2019)
Kristen Ghodsee recuperates the lost history of feminist activism from the so-called Second World, showing how women from state socialist Bulgaria and socialist-leaning Zambia created networks and alliances that challenged American women's leadership of the global women's movement